A Case of Blau Syndrome. (30th April 2014) - Chauhan, Krati; Michet, Clement
Abstract : We present a case of systemic granulomatous disorder/Blau syndrome. A patient was seen at our clinic with a diagnosis of Juvenile Idiopathic Arthritis (JIA). He was diagnosed with polyarticular JIA when he was two years old, at that time primary manifestations included inflammation of the hand and wrist joints bilaterally, later he developed ocular symptoms, which were attributed to JIA. He had liver, skin, pulmonary manifestations, and diagnostic workup including biopsy revealed granulomatous inflammation of these sites. During the diagnostic workup, he had worsening of ocular complaints, retinal exam showed panuveitis with multifocal choroiditis. These ocular findings are not seen in JIA, this, along with his other systemic manifestations, led us to revisit the diagnosis. Laboratory testing for genetic mutation for Blau syndrome was done and came back positive. Now all of his systemic findings were placed under one umbrella of systemic granulomatous syndrome/Blau syndrome. Due to worsening of ocular manifestations, he was started on Adalimumab with marked improvement of ocular and systemic manifestations and is followed by team that consists of Rheumatologist, Ophthalmologist, and Gastroenterologist.